Emotional model for a multi-robot system with emergent behavior - Gil, Angel; Aguilar, Jose; Dapena, Eladio; Rivas, Rafael (Institute of Advanced Engineering and Science, 2020)
This article describes an emotional model for a general-purpose robot operating in a multi-robot system with emergent behavior. The model considers four basic emotions: anger, rejection, sadness and joy, plus a neutral emotional state, which affect the behavior of the robot, both individually and collectively. The emotional state of each robot in the system is constructed through the conjunction of a series of factors related to their individual and collective actions, which are: safety, load, acting and interaction, which serve as input to an emotional process that results in an index of satisfaction of the robot that establishes the emotional state in which it is in a certain moment. The emotional state of a robot influences its interactions with the other robots and with the environment, that is, it determines its emergent behavior in the system. This paper presents the design of this model, and establishes some considerations for its implementation.